A molecular-dynamics study of the tensile deformation and fracture behavior of nanostructured lithium aluminum oxide. (20th February 2018) - Yu, You; Shen, Yan Hong; Zhao, Guo Dong; Zheng, Xiao Lin
Abstract: Three-dimensional nanocrystalline models of LiAlO2 with the log-normal grain size distribution are constructed with constrained Voronoi tessellation. First, the relaxation procedure of nanostructured LiAlO2 is carried out using molecular dynamics. The results suggest a reduction in the atomic densities after the relaxation process. Next, the tensile deformation and fracture behavior of nanostructured LiAlO2 are studied by using the optimized model. By researching the tensile deformation and fracture behavior of nanostructured LiAlO2, we find some interesting results: on the one hand, the greater the average grain size of the sample is, the stronger its tensile strength. On the other hand, after the strain reaches approximately 3% of the deformation of the sample, the stress of the sample does not change with the increase of the strain, displaying a plastic flow of the plastic material.